How are distractibility and hazard prediction in driving related? Role of driving experience as moderating factor. (November 2019) - Castro, Candida; Padilla, Jose-Luis; Doncel, Pablo; Garcia-Fernandez, Pedro; Ventsislavova, Petya; Eisman, Eduardo; Crundall, David
Abstract: Distraction constitute one of the 'five fatal' behaviours that contribute to road trauma, and some people may be more susceptible to it than others. It is also known that a greater ability to predict danger is related to a lower probability of suffering accidents. It could be hypothesised that drivers with a higher tendency to distraction are worse at predicting traffic hazards, but to what extent might driving experience serve to mitigate this tendency to distraction? The current study collected self-reported attentional errors from drivers by using the Attention-Related Driving Errors Scale (ARDES-Spain) in order to examine whether novice drivers suffered from inattention more than experienced drivers. The results demonstrated that novice drivers scored more highly on ARDES than experienced drivers. ARDES scores were then related to performance in a Hazard Prediction test, where participants had to report what hazard was about to happen in a series of video clips that occlude just as the hazard begins to develop. While experienced drivers were better at the Hazard Prediction test than novice drivers, those participants who reported fewer attention errors were also better able to detect the upcoming hazard following occlusion. In addition, our results demonstrate a relationship between self-reported attentional errors and the ability to predict upcoming hazards on the road, with driving experience having a moderating role. In the case of novice drivers, as their scores in the Manoeuvring Errors ARDES factor increase, their ability in Hazard Prediction diminishes, while for experienced drivers the increase is not significant. Guidance on how to improve training for drivers in order to mitigate the effects of inattention on driving safety can be addressed. Highlights: Control ARDES scores were negatively correlated to performance in the Hazard Prediction (HP) test. Driving experience plays a role in improving hazard prediction and moderating the negative effect of distraction while driving. Proneness to distraction is more negative when it affects novice drivers. Only for novice drivers, higher scores in the Manoeuvring Errors factor predict a worse hazard prediction performance..